Addressing the Anthropocene from the Global South: integrating paleoecology, archaeology and traditional knowledge for COP engagement - , ECHOES; Zuccarelli Freire, Verónica; Ziegler, Michael J.; Caetano-Andrade, Victor; Iminjili, Victor; Lellau, Rebecca; Stokes, Freg; Rudd, Rachel C.; Heberle Viegas, Danielle; Maezumi, S. Yoshi; Jha, Gopesh; Antonosyan, Mariya; et al. (Frontiers in Earth Science, 2024)
The triple planetary crisis of climate change, pollution, and biodiversity loss necessitates more holistic, comprehensive, and integrated public policy approaches. Within the United Nations Framework Convention on Climate Change, this crisis highlights significant conflicts over forms of knowledge and conceptualization, affecting how international policies are formed. Indigenous knowledge systems have become increasingly acknowledged for their vital role in addressing the challenges of the Anthropocene. Conferences of the Parties institutions like the International Indigenous Peoples Forum on Climate Change emphasize the critical, although not always recognized, importance of Indigenous territories, which contain eighty percent of the world’s biodiversity. Here, we show that research in paleoecology, archaeology and history demonstrates the long-term significance of traditional knowledge and Indigenous land management practices for contemporary ecosystem dynamics. Drawing from these varied studies and perspectives also reveal the socio-economic inequalities resulting from centuries of European colonialism. We showcase three case studies on; (i) pastoralism in eastern Africa, (ii) natural resource management in southeast Asia and (iii) adaptation to sea level rise in the Caribbean, which touch upon highly diverse human resilience strategies across space and time. Despite efforts at the COP28 to accelerate climate action and incorporate diverse knowledge systems, significant challenges remain. The need for a pluralistic knowledge, rather than a one-size-fits-all approach, blending scientific language with artistic and narrative forms, is proposed as critical for fostering effective communication and developing more effective and equitable solutions for global environmental governance.